ANALYSIS OF THE RELATIONSHIP BETWEEN ECONOMIC LAW AND HEALTH LAW IN THE PROTECTION OF HUMAN RIGHTS OF PETTY THEFT OFFENDERS - Sapta Nur Fallah; Indah Dwiprigitaningtias (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
This study aims to analyse the relationship between economic law and health law in protecting the human rights of petty theft offenders in Indonesia. The phenomenon of petty theft is often triggered by economic pressure, poverty, and limited access to basic needs and health services, especially mental health. This study uses a sociological legal research method with a descriptive-analytical approach, reviewing literature, laws and regulations, and previous research results. The results of the analysis show that economic and mental health factors are intertwined as the main triggers for petty theft, while the existing legal system still focuses on the punishment aspect rather than rehabilitation and recovery of offenders. Regulatory conflicts are also found in the application of restorative justice and human rights protection, where the rights of perpetrators and victims have not been fully accommodated fairly. This research recommends the need for policy reforms that integrate economic, health and legal approaches holistically, including strengthening mental health services and poverty alleviation programmes, in order to realise more effective and equitable human rights protection for petty theft offenders.